Preparation method of PVDF-g-DMC polymer synthesized by alkali treatment method and PVDF / PVDF-g-DMC blended membrane
By grafting DMC on PVDF and preparing PVDF/PVDF-g-DMC blended membrane, the problems of hydrophobicity and easy adsorption of PVDF ultrafiltration membrane are solved, significantly improving its hydrophilicity and anti-pollution properties, and improving water Flux and acid and alkali resistance extend the service life of the membrane.
Patent Information
- Application Number
- CN202410683107.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-30
- Publication Date
- 2025-01-07
AI Technical Summary
Because of its hydrophobicity, PVDF ultrafiltration membranes are prone to deposition and adsorption of pollutants, causing membrane pollution. The existing modification methods are difficult to effectively improve their hydrophilicity and anti-pollution properties.
Methacryloyloxyethyltrimethylammonium chloride (DMC) was grafted on PVDF by alkali treatment to form PVDF-g-DMC polymer, and blended with PVDF, and prepared by immersion precipitation phase conversion method (NIPS) PVDF/PVDF-g-DMC blended membrane improves its hydrophobicity and filtration performance.
It significantly improves the hydrophilic properties, water flux, tensile strength and acid-base resistance of PVDF/PVDF-g-DMC blended film, enhances the retention and adsorption properties of dyes, extends the service life of the film, and improves the Filtration effect on aqueous dye solution.
Smart Images

Figure CN119264333A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of dye pollutant treatment, and specifically relates to a method for synthesizing a PVDF-g-DMC polymer through an alkali treatment method, and a method for preparing a PVDF / PVDF-g-DMC blended membrane. Background Art
[0002] Water pollution is a major environmental problem facing the world today. For example, pollutants such as metals, organic matter and harmful microorganisms exist in water bodies. These pollutants include industrial wastewater discharge, agricultural pollutants, urban sewage, etc., which seriously affect people's health and aquatic ecological balance. [1-3] .
[0003] Membrane separation technology is widely used in the field of sewage treatment due to its advantages of low energy consumption, simple operation, low cost and environmental friendliness. Currently, commonly used membrane materials include cellulose, polysulfone, polyamide, polyolefin and fluorine-containing polymers. Among them, polyvinylidene fluoride (PVDF) is widely used in various fields due to its excellent chemical properties, thermal stability, mechanical properties, UV resistance, corrosion resistance and easy processing into membranes. However, due to the hydrophobicity of PVDF, it is easy to produce pollutant deposition and adsorption during water treatment, which is easy to cause membrane pollution. Therefore, improving the hydrophilicity of PVDF ultrafiltration membrane has become one of the research hotspots of many scholars.
[0004] The modification methods of PVDF ultrafiltration membrane can be roughly divided into surface modification and blending modification. Blending modification is widely used because of the advantages of more stable performance of the modified membrane, simple operation and low cost. Generally, blending modification is divided into blending modification of polymer and ceramic materials, blending modification of polymer materials and inorganic materials, and blending modification of polymer materials and polymer materials. Among them, the advantage of blending modification of polymer materials and polymer materials is not only to maintain the performance of the raw materials themselves and overcome the defects of the raw materials, but also the key lies in the ability to adjust the compatibility between polymers. Polymer materials are generally compatible with PVDF, and the use of polymer blending modification has a significant effect on improving the hydrophilicity, pure water flux and anti-pollution ability of the membrane.
[0005] Methacryloyloxyethyltrimethylammonium chloride (DMC) is widely used in papermaking, textile printing and dyeing, medicine, biology, daily chemicals, water treatment and other fields due to its high stability, good hydrophilicity and low price. However, there are few reports on the application of DMC in separation membranes. Summary of the invention
[0006] The present invention aims to solve the technical problems of strong hydrophobicity and easy pollution of PVDF ultrafiltration membrane, and provides a method for synthesizing PVDF-g-DMC polymer and preparing PVDF / PVDF-g-DMC blended membrane by alkali treatment.
[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0008] The present invention grafts hydrophilic DMC onto PVDF through an alkali treatment method to improve the hydrophobicity of PVDF itself and prepare a PVDF-g-DMC polymer. PVDF-g-DMC is used as a modifier and blended with a PVDF membrane substrate having many excellent properties to prepare a PVDF / PVDF-g-DMC blended membrane through an immersion precipitation phase inversion method (NIPS).
[0009] The object of the present invention is to provide a method for synthesizing a PVDF-g-DMC polymer by an alkali treatment method, comprising the following steps:
[0010] Step 1: Under the protection of nitrogen, polyvinylidene fluoride (PVDF) is dissolved in N-methylpyrrolidone (NMP), and then tetramethylammonium hydroxide (TMAH) is added, and the whole system is heated to 60°C for 30 minutes, and vacuum dried to complete the alkalization of PVDF;
[0011] Step 2: dissolving benzoyl peroxide (BPO) in dimethyl sulfoxide (DMSO), then pouring it into methacryloyloxyethyl trimethylammonium chloride (DMC) and alkalized PVDF, stirring at 100° C. for 48 hours and then stopping the reaction;
[0012] Step 3: After the reaction system cools to room temperature, wash it alternately with methanol and deionized water for multiple times and then dry it in vacuum to obtain a PVDF-g-DMC polymer.
[0013] It is further defined that in step 1, 3 g of polyvinylidene fluoride (PVDF) is dissolved in 20 mL of N-methylpyrrolidone (NMP), and then 0.9 mL of tetramethylammonium hydroxide (TMAH) is added.
[0014] Further defined, in step 2, 0.4 g of benzoyl peroxide (BPO) is dissolved in 15 mL of dimethyl sulfoxide (DMSO), and then poured into 4.5 mL of methacryloyloxyethyltrimethylammonium chloride (DMC) and 3 g of alkalized PVDF.
[0015] Further defined, in step 2, vacuum drying at 100° C. for 3 h;
[0016] It is further defined that in step three, vacuum drying is performed at 100° C. for 12 h.
[0017] The synthetic reaction principle of the polymer PVDF-g-DMC of the present invention is as follows:
[0018]
[0019] The object of the present invention is to provide a method for preparing a PVDF / PVDF-g-DMC blend membrane, which is carried out according to the following steps:
[0020] Step 1, drying PVDF and PVDF-g-DMC prepared by the above method respectively;
[0021] Step 2, placing the PVDF-g-DMC polymer treated in step 1 in N, N-2-methylformamide (DMF) and performing ultrasonic dispersion, adding the polymer to a mixed solution of PVDF and polyvinylpyrrolidone (PVP) after it is completely dissolved, heating at a constant temperature until a transparent and uniform casting solution is formed, standing for degassing, and obtaining a casting solution;
[0022] Step 3: Evenly cast the casting liquid on a smooth and clean glass plate, scrape the film at a constant speed, let it stand for a while, and after the casting liquid is evenly spread on the glass plate, place it vertically in deionized water to phase-convert into a membrane. Soak the membrane in deionized water to remove residual solvent on the membrane surface and in the membrane pores.
[0023] It is further defined that in step 2, 0.1 g of the PVDF-g-DMC polymer treated in step 1 is placed in 10 mL of N,N-2-methylformamide (DMF) and ultrasonically dispersed, and after it is completely dissolved, it is added to a mixed solution of 13 g of PVDF and 0.9 g of polyvinyl pyrrolidone (PVP).
[0024] It is further defined that in step 2, the heating is performed at a constant temperature of 60°C-80°C for 6h-10h.
[0025] It is further defined that in step 3, the soaking time is 24 hours.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] When the PVDF content is 13wt.%, the PVP content is 0.9wt.%, the PVDF-g-DMC content is 1wt.%, the stirring time is 8h, and the stirring temperature is 70℃. Under this condition, the water flux of the PVDF / PVDF-g-DMC blend membrane is 353.63L / m 2 h, the rejection rate is 90.61%, the average pore size is 64.24 nm, and the porosity is 61.71%.
[0028] Compared with PVDF ultrafiltration membrane, the water contact angle of PVDF / PVDF-g-DMC blend membrane is reduced by 6.17°, and the hydrophilicity is significantly improved. The tensile strength of PVDF / PVDF-g-DMC blend membrane is 2.86N / mm 2, the elongation at break is 46.67%, which meets the mechanical property requirements. After being immersed in acid and alkali solutions for four weeks, the decrease in water flux of the PVDF / PVDF-g-DMC blend membrane is less than that of the PVDF ultrafiltration membrane, and the acid and alkali resistance is improved. The adsorption amount of BSA by the PVDF / PVDF-g-DMC blend membrane is small, the flux recovery rate is high (72.39%), and the anti-pollution performance is good. After multiple cycles of filtration, the water flux of the PVDF / PVDF-g-DMC blend membrane is still 134.25L / m higher than that of the PVDF ultrafiltration membrane. 2 h, good long-term stability.
[0029] The flux of PVDF / PVDF-g-DMC blend membrane for CR, MB, and NR is higher than that of PVDF ultrafiltration membrane, which is 200.42 L / m 2 h, 246.28L / m 2 h, 287.05L / m 2 h; The retention rates of PVDF / PVDF-g-DMC blended membranes for CR, MB, and NR dyes are higher than those of PVDF ultrafiltration membranes, which are 89.15%, 70.99%, and 62.5%, respectively, and the filtration effect on dye aqueous solutions is better. The adsorption amount of CR, MB, and NR dyes by PVDF / PVDF-g-DMC blended membranes is always less than that of PVDF ultrafiltration membranes; The flux recovery rates of CR, MB, and NR dyes by PVDF / PVDF-g-DMC blended membranes are higher than those of PVDF ultrafiltration membranes, which are 72.46%, 82.86%, and 91.95%, respectively. The modified PVDF / PVDF-g-DMC blended membranes have a higher anti-dye pollution effect. After multiple cycles of filtration, the flux changes of CR, MB, and NR by PVDF / PVDF-g-DMC blended membranes are smaller than those of PVDF ultrafiltration membranes, and the modified PVDF / PVDF-g-DMC blended membranes have better long-term stability for treating dye aqueous solutions.
[0030] The addition of PVDF-g-DMC comprehensively improves the filtration performance, hydrophilicity, mechanical properties, corrosion resistance, anti-pollution performance and long-term stability of the PVDF / PVDF-g-DMC blend membrane, and has a good effect on dye treatment. It is expected to become a new separation membrane with excellent comprehensive performance and can be put into use for a long time.
[0031] In order to further understand the features and technical contents of the present invention, please refer to the following detailed description and drawings of the present invention. However, the attached drawings are only provided for reference and illustration and are not intended to limit the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 is the EDS pattern of PVDF-g-DMC polymer;
[0033] Figure 2 is the EDS image of PVDF-g-DMC;
[0034] Figure 3 Surface SEM images of PVDF ultrafiltration membrane (a) and PVDF / PVDF-g-DMC blend membrane (b)
[0035] Figure 4 The cross-sectional SEM images of PVDF ultrafiltration membrane (a) and PVDF / PVDF-g-DMC (b) blend membrane;
[0036] Figure 5 The water flux of PVDF ultrafiltration membrane and PVDF / PVDF-g-DMC blend membrane varies with the immersion time in hydrochloric acid solution with pH = 2;
[0037] Figure 6 The flux changes of PVDF ultrafiltration membrane and PVDF / PVDF-g-DMC blend membrane immersed in alkaline solution;
[0038] Figure 7 is the change of BSA static adsorption capacity of PVDF ultrafiltration membrane and PVDF / PVDF-g-DMC blend membrane;
[0039] Figure 8 The change of membrane water flux over time during three cycles of filtration and backwashing (fouling type: 1g / L BSA). DETAILED DESCRIPTION
[0040] The present invention will be described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, and do not limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention. These all fall within the scope of protection of the present invention.
[0041] Example 1: In this example, PVDF-g-DMC polymer is synthesized by alkali treatment, comprising the following steps:
[0042] Step 1: Under the protection of nitrogen, 3 g of polyvinylidene fluoride (PVDF) was dissolved in 20 mL of N-methylpyrrolidone (NMP), and 0.9 mL of tetramethylammonium hydroxide (TMAH) was added. The whole system was heated to 60 ° C for 30 min, and vacuum dried at 100 ° C for 3 h to complete the alkalization of PVDF.
[0043] Step 2: Dissolve 0.4 g of benzoyl peroxide (BPO) in 15 mL of dimethyl sulfoxide (DMSO), then pour it into 4.5 mL of methacryloyloxyethyl trimethylammonium chloride (DMC) and 3 g of alkalized PVDF, and stir at 100 ° C for 48 hours before stopping the reaction;
[0044] Step 3: After the reaction system cools to room temperature, wash it alternately with methanol and deionized water for multiple times and then vacuum dry it at 100° C. for 12 h to obtain PVDF-g-DMC polymer.
[0045] The FT-IR spectra of PVDF and PVDF-g-DMC polymers are shown in Figure 1 As shown. Figure 1 It can be seen that compared with PVDF, PVDF-g-DMC polymer has a -1 A new absorption peak appears at 1072cm, which is the carbonyl C=O stretching vibration on DMC. -1 The absorption peak at 977cm is enhanced, which is due to the stretching vibration of CF generated by part of CF2. -1 、801cm -1 、760cm -1 The characteristic absorption peak of the PVDF crystalline phase at the position was weakened and shifted. This indicates that DMC was successfully grafted onto PVDF to synthesize the polymer PVDF-g-DMC.
[0046] The EDS image of PVDF-g-DMC polymer is shown in Figure 2 As shown. Figure 2 It can be seen that the polymer contains C, F, N, O, and Cl elements, among which C and F come from PVDF, and N, O, and Cl come from DMC, which proves that DMC is successfully grafted onto PVDF to synthesize the polymer PVDF-g-DMC.
[0047] Example 2: The preparation method of the PVDF / PVDF-g-DMC blend membrane in this example is carried out according to the following steps:
[0048] Step 1, drying PVDF and PVDF-g-DMC prepared by the method of claim 1 respectively, both at 100° C. for 3 h;
[0049] Step 2, 0.1 g of the PVDF-g-DMC polymer treated in step 1 is placed in 10 mL of N, N-2-methylformamide (DMF) and ultrasonically dispersed. After it is completely dissolved, it is added to a mixed solution of 13 g of PVDF and 0.9 g of polyvinyl pyrrolidone (PVP), and heated at a constant temperature of 70° C. until a transparent and uniform casting solution is formed, and the casting solution is allowed to stand for degassing to obtain a casting solution;
[0050] Step 3: Cast the casting liquid evenly on a smooth and clean glass plate, scrape the film at a constant speed, and let it stand for a while. After the casting liquid flows evenly on the glass plate, place it vertically in deionized water to form a membrane. Soak the membrane in deionized water for 24 hours to remove the residual solvent on the membrane surface and in the membrane pores.
[0051] The PVDF content was 13wt.%, the PVP content was 0.9wt.%, the PVDF-g-DMC content was 1wt.%, the stirring time was 8h, and the stirring temperature was 70°C.
[0052] The water flux of the PVDF / PVDF-g-DMC blend membrane in this example is 353.63 L / m 2 h, the rejection rate is 90.61%. The addition of PVDF-g-DMC improves the filtration performance of PVDF / PVDF-g-DMC blend membrane. For PVDF / PVDF-g-DMC blend membrane, the average pore size is 64.24nm, and the porosity is 61.71%. Compared with PVDF ultrafiltration membrane, the average pore size and porosity are increased and the pore size distribution is more uniform. The membrane surface potential of PVDF / PVDF-g-DMC blend is -27.5mv at pH=7.
[0053] The surface SEM images of PVDF ultrafiltration membrane and PVDF / PVDF-g-DMC blend membrane are shown in Figure 3 As shown. Figure 3 It can be seen that the number of membrane pores on the surface of PVDF / PVDF-g-DMC blend membrane is increased compared with that on the surface of PVDF ultrafiltration membrane, and the pore distribution on the surface of PVDF / PVDF-g-DMC blend membrane is more uniform, and there are no defective macropores.
[0054] The cross-sectional SEM images of PVDF ultrafiltration membrane and PVDF / PVDF-g-DMC blend membrane are shown in Figure 2. Figure 4 As shown by Figure 4 It can be seen that PVDF ultrafiltration membrane ( Figure 4 (a)) and PVDF / PVDF-g-DMC blend membranes ( Figure 4 (b)) are composed of a dense microporous skin layer that plays a separation role and a macroporous layer that plays a supporting role, which is a typical asymmetric structure. However, the difference is that the hydrophilicity of PVDF-g-DMC accelerates the phase conversion rate of PVDF / PVDF-g-DMC blend membranes, thereby increasing the finger-like pores in the cross section of the PVDF / PVDF-g-DMC blend membranes. Figure 2-8 The results are consistent.
[0055] Table 1 Pore size and porosity of PVDF ultrafiltration membrane and PVDF / PVDF-g-DMC blend membrane ( n=3)
[0056]
[0057] As shown in Table 1, the average pore size of the PVDF ultrafiltration membrane is 56.03nm, the porosity is 52.8%, and the average pore size of the PVDF / PVDF-g-DMC blend membrane is 64.24nm, and the porosity is 61.71%. The average pore size of the PVDF / PVDF-g-DMC blend membrane is 8.21nm larger than that of the PVDF ultrafiltration membrane, and the porosity is 8.91% higher. This is because the hydrophilicity of PVDF-g-DMC accelerates the phase conversion rate of the membrane, thereby increasing the pore size and porosity of the PVDF / PVDF-g-DMC blend membrane, and improving its permeability.
[0058] The average water contact values of PVDF ultrafiltration membrane and PVDF / PVDF-g-DMC blend membrane were 77.4° and 71.23°, respectively.
[0059] The tensile strength of PVDF ultrafiltration membrane and PVDF / PVDF-g-DMC blend membrane are 2.99N / mm 2 , 2.86N / mm 2 The tensile strength of the two membranes is not much different; the elongation at break of PVDF ultrafiltration membrane and PVDF / PVDF-g-DMC blend membrane are 32% and 46.67% respectively. The elongation at break of PVDF / PVDF-g-DMC blend membrane is 14.67% higher than that of PVDF ultrafiltration membrane. The addition of PVDF-g-DMC to PVDF increases the elongation at break of PVDF / PVDF-g-DMC blend membrane ultrafiltration membrane.
[0060] Figure 1 shows the variation trend of water flux of PVDF ultrafiltration membrane and PVDF / PVDF-g-DMC blend membrane with immersion time in hydrochloric acid solution with pH = 2. Figure 5 As shown. Figure 5 It can be seen that after immersion in acid solution for 1 week, 2 weeks, 3 weeks, and 4 weeks, the water flux of PVDF ultrafiltration membrane is 178.34 L / m 2 h, 165.1L / m 2 h, 147.77L / m 2 h, 137.58L / m 2 ·h, the water flux after immersion for 4 weeks decreased by 35.71% compared with that after immersion for 0 weeks; for PVDF / PVDF-g-DMC blend membrane, the water flux was 305.73 L / m 2 h, 290.45L / m 2 h, 273.12L / m 2 h, 264.97L / m 2h, the water flux after immersion for 4 weeks decreased by 24.64% compared with the water flux after immersion for 0 weeks. It can be seen that the water flux of PVDF ultrafiltration membrane and PVDF / PVDF-g-DMC blend membrane decreased after being immersed in acid solution, but the PVDF ultrafiltration membrane decreased faster. This is because the acid solution will destroy the internal structure of PVDF ultrafiltration membrane and PVDF / PVDF-g-DMC blend membrane, resulting in a decrease in the water flux of both, but the introduction of PVDF-g-DMC enhances the acid resistance of PVDF / PVDF-g-DMC blend membrane, enabling it to maintain a relatively high acid resistance.
[0061] The water flux of PVDF ultrafiltration membrane and PVDF / PVDF-g-DMC blend membrane changes with the immersion time in sodium hydroxide solution at pH = 14. Figure 6 .Depend on Figure 6 It can be seen that after soaking in alkaline solution for 1 week, 2 weeks, 3 weeks, and 4 weeks, the water flux of PVDF ultrafiltration membrane is 168.15 L / m 2 h, 145.73L / m 2 h, 132.48L / m 2 h, 124.33L / m 2 ·h, the water flux after immersion for 4 weeks decreased by 43.26% compared with that after immersion for 0 weeks; for PVDF / PVDF-g-DMC blend membrane, the water flux was 297.58 L / m 2 h, 280.25L / m 2 h, 262.93L / m 2 h, 244.59L / m 2 h, the water flux after immersion for 4 weeks decreased by 31.43% compared with the water flux after immersion for 0 weeks. It can be seen that the water flux of PVDF ultrafiltration membrane and PVDF / PVDF-g-DMC blend membrane decreased after immersion in alkali solution, but the PVDF ultrafiltration membrane decreased faster. This is because the internal structure of PVDF ultrafiltration membrane and PVDF / PVDF-g-DMC blend membrane will be destroyed after immersion in alkali solution, resulting in a decrease in water flux. The addition of PVDF-g-DMC enhances the alkali resistance of PVDF / PVDF-g-DMC blend membrane, enabling it to maintain a relatively high alkali resistance.
[0062] The adsorption capacity of PVDF ultrafiltration membrane and PVDF / PVDF-g-DMC blend membrane after being immersed in BSA solutions of different concentrations for 24 h is shown in Figure 2. Figure 7 As shown. Figure 7It can be seen that with the increase of BSA solution concentration, the adsorption amount of BSA by PVDF ultrafiltration membrane and PVDF / PVDF-g-DMC blend membrane also gradually increased. At the same BSA concentration, the adsorption amount of PVDF ultrafiltration membrane is always greater than that of PVDF / PVDF-g-DMC blend membrane. The addition of PVDF-g-DMC modifier improves the hydrophilicity of PVDF / PVDF-g-DMC blend membrane. When PVDF / PVDF-g-DMC blend membrane contacts water, it can form a hydration layer, which reduces the contact probability of BSA with the membrane surface, making it difficult for BSA macromolecular protein to adsorb to the membrane surface.
[0063] The average roughness Ra of PVDF ultrafiltration membrane and PVDF / PVDF-g-DMC blend membrane are 27.87nm and 29.1nm respectively; the root mean square roughness Rq of PVDF ultrafiltration membrane and PVDF / PVDF-g-DMC blend membrane are 34.83nm and 37nm respectively; the distance Rmax between the highest peak and the lowest valley of PVDF ultrafiltration membrane and PVDF / PVDF-g-DMC blend membrane are 220.33nm and 288.67nm respectively. Compared with PVDF ultrafiltration membrane, Ra, Rq and Rmax of PVDF / PVDF-g-DMC blend membrane have increased, but the average roughness of PVDF / PVDF-g-DMC blend membrane has only increased by 1.23nm. In summary, the membrane roughness does not change much before and after PVDF-g-DMC modification of PVDF ultrafiltration membrane.
[0064] The changes in water flux of PVDF ultrafiltration membrane and PVDF / PVDF-g-DMC blend membrane after three cycles of water-BSA solution-water filtration are shown in the figure. Figure 8 .Depend on Figure 8 It can be seen that the water flux of PVDF ultrafiltration membrane and PVDF / PVDF-g-DMC blend membrane after the first filtration of pure water is 213.59 L / m 2 h, 363.10L / m 2 ·h, after the second filtration of pure water, the water flux of the two were 131.20L / m 2 h, 268.51L / m 2 ·h, after the third filtration of pure water, the pure water flux of the two were 125.1L / m 2 h, 259.35L / m 2 ·h, after the fourth filtration of pure water, the pure water flux of the two were 122.05L / m 2 h, 256.30L / m 2·h. It can be seen that the water flux of the PVDF ultrafiltration membrane and PVDF / PVDF-g-DMC blend membrane for the fourth filtration of pure water decreased by 42.86% and 29.41% respectively compared with the first filtration, and the water flux change of the PVDF / PVDF-g-DMC blend membrane was relatively small. This is because the addition of PVDF-g-DMC improves the hydrophilicity of the PVDF / PVDF-g-DMC blend membrane, making it difficult for pollutants to remain on the surface of the membrane and some pollutants remaining on the surface of the membrane are easily removed, thereby improving the anti-pollution performance of the PVDF / PVDF-g-DMC blend membrane, so that it can still maintain a high water flux and a relatively stable flux change during a long period of filtration.
[0065] The flux of PVDF / PVDF-g-DMC blend membrane for CR, MB, and NR is 200.42 L / m 2 h, 246.28L / m 2 h, 287.05L / m 2 h, the flux of CR, MB and NR was higher than that of PVDF ultrafiltration membrane; the retention rates of CR, MB and NR of PVDF / PVDF-g-DMC blend membrane were 89.15%, 70.99% and 62.5%, respectively, which were higher than those of PVDF ultrafiltration membrane. Under the condition of the same dye concentration, the adsorption amount of CR, MB and NR of PVDF / PVDF-g-DMC blend membrane was always less than that of PVDF ultrafiltration membrane; the flux recovery rate of CR, MB and NR of PVDF / PVDF-g-DMC blend membrane was 72.46%, 82.86% and 91.95%, respectively, which was higher than that of PVDF ultrafiltration membrane. After multiple cycles of filtration, the flux change rate of PVDF / PVDF-g-DMC blend membrane was small and the long-term stability was better.
[0066] The above describes the specific embodiments of the present invention. It should be noted that the present invention is not limited to the above specific embodiments, and those skilled in the art can make various modifications or variations within the scope of the claims, which does not affect the essential content of the present invention.
Claims
1. Synthesis of PVDF-g-DMC polymer by alkali treatment, characterized in that: The following steps are involved: Step 1: Under the protection of nitrogen, polyvinylidene fluoride (PVDF) is dissolved in N-methylpyrrolidone (NMP), and then tetramethylammonium hydroxide (TMAH) is added, and the whole system is heated to 60°C for 30 minutes, and vacuum dried to complete the alkalization of PVDF; Step 2: dissolving benzoyl peroxide (BPO) in dimethyl sulfoxide (DMSO), then pouring it into methacryloyloxyethyl trimethylammonium chloride (DMC) and alkalized PVDF, stirring at 100° C. for 48 hours and then stopping the reaction; Step 3: After the reaction system cools to room temperature, wash it alternately with methanol and deionized water for multiple times and then dry it in vacuum to obtain a PVDF-g-DMC polymer.
2. The method according to claim 1, characterized in that: In step 1, 3 g of polyvinylidene fluoride (PVDF) was dissolved in 20 mL of N-methylpyrrolidone (NMP), and 0.9 mL of tetramethylammonium hydroxide (TMAH) was added.
3. The method according to claim 2, characterized in that: In step 2, 0.4 g of benzoyl peroxide (BPO) was dissolved in 15 mL of dimethyl sulfoxide (DMSO), and then poured into 4.5 mL of methacryloyloxyethyltrimethylammonium chloride (DMC) and 3 g of alkalized PVDF.
4. The method according to claim 1, characterized in that: In step 2, vacuum drying was performed at 100° C. for 3 h.
5. The method according to claim 1, characterized in that: In step 3, vacuum drying was performed at 100° C. for 12 h.
6. A method for preparing a PVDF / PVDF-g-DMC blend membrane, characterized in that: The method is carried out according to the following steps: Step 1, drying PVDF and PVDF-g-DMC prepared by the method according to any one of claims 1 to 5 respectively; Step 2, placing the PVDF-g-DMC polymer treated in step 1 in N, N-2-methylformamide (DMF) and performing ultrasonic dispersion, adding the polymer to a mixed solution of PVDF and polyvinylpyrrolidone (PVP) after it is completely dissolved, heating at a constant temperature until a transparent and uniform casting solution is formed, standing for degassing, and obtaining a casting solution; Step 3: Evenly cast the casting liquid on a smooth and clean glass plate, scrape the film at a constant speed, let it stand for a while, and after the casting liquid is evenly spread on the glass plate, place it vertically in deionized water to phase-convert into a membrane. Soak the membrane in deionized water to remove residual solvent on the membrane surface and in the membrane pores.
7. The method according to claim 6, characterized in that: In step 2, 0.1 g of the PVDF-g-DMC polymer treated in step 1 is placed in 10 mL of N,N-2-methylformamide (DMF) and ultrasonically dispersed. After it is completely dissolved, it is added to a mixed solution of 13 g of PVDF and 0.9 g of polyvinyl pyrrolidone (PVP).
8. The method according to claim 6, characterized in that: In step 2, the temperature is kept constant at 60°C-80°C.
9. The method according to claim 6, characterized in that: In step 3, the soaking time is 24 hours.